Capital structure, capital investment and profitability among Malaysian listed firms - Vaicondam, Yamunah; Ramakrishnan, Ramakrishnan (International Journal of Engineering and Technology, 2018)
Capital investments are referred as a critical managerial decision on firm’s fixed asset for generating profitability. However, the empirical finding shows that not every capital investment has a significant positive effect on profitability. Literature indicates mixed results of examining the capital investment relationship with firm’s profitability, which vary in respects to the debt structure. On the other hand, strong government reinforcement has pushed Malaysia up as one of the top ten countries with robust private capital investment in the year 2004. Since the capital investments are typically irreversible and hypothesized as profit generator, the first aim of this study is to examine the effect of the capital investment on the firm’s profitability across firms and sectors. The second aim is to examine the moderating effect of capital structure on the relationship between capital investment and profitability across firms and sectors. This study utilized pooled ordinary least squares and fixed effect analysis across 708 non-financial Malaysian listed firms. The unbalanced datasets for the period 2001 to 2015 were employed to check the robustness of these results. This study suggested that capital investment has a strong significant positive effect on profitability measurements across Malaysian listed firms in non-financial sectors. On the other hand, the significant negative moderating effect of capital structure on the relationship between capital investment and return on capital across Malaysian listed firms reflected the perspective of empire building theory. In addition, the independent sample test engaged across sectors affirmed that moderating effect of capital structure are different across sectors. Thus, this study concluded the existence of moderating effect of capital structure on the relationship between capital investment and profitability. This study addressed the knowledge gap on the moderating effect of capital structure based on empire building theory.